Host Cognition and Parasitism in Birds: A Review of the Main Mechanisms - Ducatez, Simon; Lefebvre, Louis; Sayol, Ferran; Audet, Jean-Nicolas; Sol, Daniel (Frontiers in Ecology and Evolution, 2020)
Parasites can have important detrimental effects on host fitness, thereby influencing their ecology and evolution. Hosts can, in turn, exert strong selective pressures on their parasites, affecting eco-evolutionary dynamics. Although the reciprocal pressures that hosts and parasites exert on each other have long been recognised, the mechanisms are insufficiently understood. Here, we discuss the role of host cognition in host-parasite eco-evolutionary dynamics. Theoretical advances have acknowledged the importance of behaviour in shaping these dynamics, but how and why host cognition should affect and/or be affected by parasites is less clear. We propose three scenarios that may create causal and non-causal links between cognition and the richness, prevalence and intensity of parasites. First, host cognition may change the probability of exposure to parasites, either increasing (e.g., altering the relationship with the environment via innovative behaviours) or decreasing (e.g., influencing decision-making to avoid infected conspecifics) exposure. Second, parasites may change host cognitive performance, for example by reducing host condition. Finally, host cognition and parasites can be associated via common causal factors (e.g., shared molecular pathways), energetic constraints generating trade-offs between cognition and immunocompetence, or trait co-evolution with life history, ecological or social strategies. The existence of such a variety of non-mutually exclusive mechanisms suggests that host cognition has a great potential to affect and be affected by parasites. However, it also implies that progress in understanding these effects will only be possible if we distinguish between causal and non-causal links.